Pengaruh Current Ratio, Debt to Asset Ratio, Firm Size dan Perputaran Modal Kerja Terhadap Profitabilitas (ROA) Pada Perusahaan Wholesale dan Retail Trade Yang Terdaftar Di Bursa Efek Indonesia Pada Periode 2013-2017 - Nopita Sari; Rika Malia; Ronald Hasudungan Rajagukguk; Ivana Ivana; Selin Govinna; Mas Intan Purba (Politeknik Ganesha Medan, 2019)
This study aims to determine whether there is a partial influence Current Ratio, Debt To Asset Ratio, Firm Size and Working Capital Turnover Against Profitability (ROA). This study uses quantitative research. The population in this study were all Wholesale and Retail trade companies listed on the Indonesia Stock Exchange (IDX) and continuously published financial reports in 2013-2017. Based on the purposive sampling method, the samples obtained were 20 companies for each year in the period 2013-2017, so that the data obtained were 100 observation data. The analytical method used is multiple regression analysis. The results of the study state that partially the Current Ratio, Debt to Asset Ratio, Firm size, and working capital turnover have an effect on profitability (ROA).